PERAN WORLD WIDE FUND FOR NATURE (WWF) DALAM MENGATASI PERBURUAN BADAK DI ZIMBABWE TAHUN 2015 - Paramita Sari; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study is to examine the role of the World Wide Fund for Nature (WWF) in dealing the poaching of rhinos in Zimbabwe. The country has the third largest rhino herd in Southern Africa. The country's endangered rhino population makes the WWF as an environmental organization that also address the issue of endangered species, participating in efforts to conserve this species. Poaching is a major problem in Zimbabwe. In 2015, poachers killed 51 rhinos in Zimbabwe. WWF is the world’s leading independent conservation organisation. WWF works in 100 countries and is supported by more than one million members in the United States and close to five million globally. WWF's unique way of working combines global reach with a foundation in science, involves action at every level from local to global, and ensures the delivery of innovative solutions that meet the needs of both people and nature. WWF began operations in Zimbabwe in 1983.The research method used in this study is library research method. Most of the data collected through library research, online data retrieval, books, journals, literature and document. The data was then analyzed with theoretical approaches associated with theories of International Relations such as the International Organizations Role Theory.The study concluded that WWF has done his role as international organizations in dealing the poaching of rhinos in Zimbabwe. WWF in collaboration with Zimbabwe Government to establish The Lowveld Rhino Conservancy Project (LRCP), rhino translocation, habitat management, dehorning, rhino patrol, protect conservation area, application DNA profiling of rhino horn for Forensic analysis, and Strengthening Local and International Law Enforcement. WWF also to establish The African Rhino Programme. WWF and TRAFFIC has been monitoring the rhino trade. WWF Promotes Wildlife-Based Tourism.Keywords: WWF, Rhino Poaching, Government, Zimbabwe